Analisis Sifat Korosi Galvanik Berbagai Plat Logam di Laboratorium Metalurgi Politeknik Negeri Batam - Ari Wibowo (Politeknik Negeri Batam, 2016)
Metal plates have been widely used for practical study in metallurgy laboratory at Batam polytechnic. The metals are low carbon steel, stainless steel, galvanized zinc, aluminum and copper. Two different metals adjacent to each other have very big possibility of corrosion. The corrosion is called galvanic corrosion. Corrosion that occurs between two metals that have a potential difference. In this study, five metal plates were cut with a size of about 20 mm x 150 mm with a thickness 2 mm. Then measured the voltage of the two plates that had been dipped in a 3% NaCl salt solution with a voltmeter. From the results of these measurements take two pairs of metal that has the highest voltage and the lowest. Two pairs of metal that have been subsequently dipped in a 3% salt solution and allowed to stand for 7 days to calculate the corrosion rate. From the measurement results obtained copper-zinc couple has galvanized highest voltage of 0.6 volts and a pair of zinc-aluminium has a lowest galvanized voltage of 0.05 volts and corrosion rate obtained at the highest voltage is 1.457 mm / year and the lowest was 1.457 mm / year.